Use of Heat from Wastewater. (June 2019) - Hrabová, K; Hrdlička, T; Tlašek, M
Abstract: There are increasing demands on energy efficiency at all areas of life e.g. heating, cooling and hot water supply. Using waste water is meeting requirements of sustainability and environmental protection. Waste water has great energy potential. The article deals with the optimization of sewer heat exchanger and economic efficiency. Heat exchanger effect is depending on shape and geometry of heat exchanger. Also temperature of waste water affects heat exchanger effect. Usual temperature of sewage is about 20 degrees Celsius in summer and about 10 degrees Celsius in winter. Cooling for a maximum about 1 degrees Celsius and flow at least 10 litters per second is required for seamless operation. To pass requirement of minimum flow is this system suitable for bigger buildings. It is also necessary for positive economic effect. For proper design and optimization it is necessary to use three basic methods: diagnostics, heat balance calculations and modelling. Numeric simulations are made for selection of the best sewer heat recovery. Recovered heat energy was used for heating, cooling also for hot water supply. Positive economic effect is provided in case study of administrative building.